Age Differences in Overlapping-Task Performance: Evidence for Efficient Parallel Processing in Older Adults. - Allen, Philip A.; Lien, Mei-ching; Murphy, Martin D. (Psychology & Aging, 2002)
Two psychological refractory period (PRP) experiments were conducted to examine overlapping processing in younger and older adults. A shape discrimination task (triangle or rectangle) for Task 1 (T1) and a lexical-decision task (word or nonword) for Task 2 (T2) were used. PRP effects, response time for T2 increasing as stimulus onset synchrony (SOA) decreased, were obtained for both age groups. The effect of word frequency on T2 was smaller at the short SOA than at the long SOA, reflecting slack effects, which were larger for older than younger adults in both experiments. These results suggest that older adults can perform lexical access of T2 in parallel with the processing of T1 at least as efficiently as younger adults. Reprinted by permission of the publisher.